2009
DOI: 10.1177/039463200902200409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PD98059, a Selective MAPK3/MAPK1 Inhibitor, on Acute Lung Injury in Mice

Abstract: The aim of the present study is to evaluate the contribution of mitogen-activated protein kinase 1–3 (MAPK3/MAPK1) in a model of acute lung inflammation in mice. Injection of carrageenan into the pleural cavity of mice elicited an acute inflammatory response characterized by: accumulation of fluid containing a large number of neutrophils (PMNs) in the pleural cavity, infiltration of PMNs in lung tissues and subsequent adhesion molecule expression (I-CAM and P-selectin), lipid peroxidation, and increased produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…These include the genes for TNF-α, IL-1β and iNOS to name but a few [19]. There is good evidence that IL-1β help to propagate the extension of a local or systemic inflammatory process [20]. We have clearly confirmed a significant increase in the IL-1β production in the pleural 8 days following ligation.…”
Section: Discussionsupporting
confidence: 62%
“…These include the genes for TNF-α, IL-1β and iNOS to name but a few [19]. There is good evidence that IL-1β help to propagate the extension of a local or systemic inflammatory process [20]. We have clearly confirmed a significant increase in the IL-1β production in the pleural 8 days following ligation.…”
Section: Discussionsupporting
confidence: 62%
“…; Calbiochem, San Diego, CA), a potent and selective antagonist of MEK-1, which is the upstream kinase of ERK 1/2 [28], [29]. The dose of PD98059 used is well established and has been widely used in many animal models to block the effect of ERK 1/2 [18], [30], [31], [32], [33], [34]. PD98059 or vehicle (DMSO) was administrated to mice 1 hour before CLP.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, our workgroup has already demonstrated the beneficial effects of PD98059 (2-(2-amino-3-methoxyphenyl)-4H-1-benzopyran-4-one), a highly selective inhibitor of MEK1 activation (and, consequently, of the MAP kinase cascade), showing that at a dose of 10 mg/kg, this molecule is efficient in limiting the acute lung injury induced by carrageenan (Di Paola et al 2009). …”
Section: Introductionmentioning
confidence: 98%